Reliability of a Novel Qualitative Assessment Tool for Evaluating a Run Plant Task. - Butler, Lauren; Erdman, Ashley; Martinez, Alexa; Tate, Sierra; DeVerna, Amie; Ulman, Sophia (International Journal of Sports Physical Therapy, 2026)
BACKGROUND: Young female athletes have a substantial risk of suffering an anterior cruciate ligament (ACL) injury, in part due to sex-specific movement patterns. Injury prevention strategies targeting movement errors during a deceleration task may help decrease the associated risk. In order to enhance preventive interventions, screening tools to identify at-risk individuals are vital. HYPOTHESIS/PURPOSE: To assess intra- and inter-rater reliability of a qualitative assessment of trunk and lower extremity alignment during a run plant task. It was hypothesized that the tool would demonstrate good to excellent intra- and inter-rater reliability. STUDY DESIGN: Repeated measures METHODS: Two Raters assessed videos of 25 healthy female athletes (ages 12-17 years) performing a run plant task. Female athletes were chosen due to their increased ACL injury risk. Raters used a qualitative checklist to assess trunk and lower extremity alignment, awarding one point for each observed movement fault. Item scores were then summed to generate a total score. Each video was scored twice with a two-week washout period in-between. Intraclass correlation coefficients (ICC) for each scoring item and the overall total score were calculated with a 2-way mixed-effect model and 95% confidence intervals (95% CIs) for inter- and intra-rater reliability. RESULTS: Intra-rater reliability was poor to moderate (Rater 1 ICC = 0.43, 95% CI 0.12-0.73; Rater 2 ICC = 0.54, 95% CI 0.20-0.87). Inter-rater reliability was moderate in round one (ICC = 0.66, 95% CI 0.41-0.90) and poor in round two (ICC = 0.32, 95% CI 0.02-0.63). Medial foot position was the only item to achieve good intra- and inter-rater reliability. Sagittal alignment also demonstrated good inter-rater reliability. In both rounds, dynamic valgus and preparatory deceleration steps were consistently marked as present (100% agreement), and lateral foot position was consistently marked as not present (100% agreement), by both Raters for all athletes. CONCLUSION: While some individual items showed good reliability, several items and the total score failed to achieve acceptable reliability. Despite lower ICC values for dynamic valgus, preparatory deceleration steps, and lateral foot position, percent agreement was high. The skew and limited variability in these items likely influenced ICC estimates, suggesting that Rater consistency may be underestimated. Refinement of scoring item definitions for these items is needed prior to clinical application of the tool. LEVEL OF EVIDENCE: Level 2, diagnosis